Use of Big Data and Business Intelligence Platforms to Boost the Tourism and Travel Sector in the Province of Fianarantsoa, Madagascar - Razafindrazanakolona A.D.; Raharijaona A.; Rakotonirina M. D. L.; Ramanampisoa V.E.; Rabesiaka R.; Koto-te-Nyiwa Ngbolua; Robijaona Rahelivololoniaina B.; Muhammad Ridwan (Economit Journal: Scientific Journal of Accountancy, Management and Finance, 2023)
The dynamization of Tourism in the Haute Matsiatra Region (Isalo, Andringitra, Ranomafana) is considered favorable to the promotion of Tourism and important for the sustainable development of the rural areas concerned. They are exploited by local visitors. However, currently, there is an inspiration for new openings and new and more original horizons throughout Madagascar. The idea of launching the "dynamization of tourism", using Big Data and Business Intelligence, is somewhat conceived as an exclusive speech to incite tourists to discover new destinations even more authentic than many others. However, we would like to propose that the aim of the dynamization of tourism is to make the assets dynamic, to valorize and capitalize on the natural wealth of the region for the purpose of tourism, and to develop the areas in a sustainable way.